Comparação de quatro métodos de avaliação da estabilidade fenotípica de cultivares de feijão - MIRANDA, GLAUCO VIEIRA; Cruz, Cosme Damião; Vieira, Clibas; Araújo, Geraldo A. de Andrade (Revista Ceres, 2015)
-